Estrogens as Antioxidant Modulators in Human Fertility. (20th November 2013) - Mancini, A.; Raimondo, S.; Persano, M.; Di Segni, C.; Cammarano, M.; Gadotti, G.; Silvestrini, A.; Pontecorvi, A.; Meucci, E.
Abstract : Among treatments proposed for idiopathic male infertility, antiestrogens, like tamoxifen, play a possible role. On the other hand, oxidative stress is a mechanism well recognized for deleterious effects on spermatozoa function. After reviewing the literature on the effects of estrogens in modulation of antioxidant systems, in both sexes, and in different in vivo and in vitro models, we suggest, also on the basis of personal data, that a tamoxifen treatment could be active via an increase in seminal antioxidants.